(untitled) (Ta’limning zamonaviy transformatsiyasi, 2024)
The article provides an insightful exploration of the life and literary contributions of Sir Francis Bacon, and a leading figure of the English Renaissance, revolutionized the way we understand and investigate the natural world. As the father of empiricism, he challenged traditional Aristotelian logic and championed a new scientific method based on observation, experimentation, and inductive reasoning. His groundbreaking work, exemplified in *Novum Organum*, laid the foundation for the scientific revolution and continues to influence scientific inquiry today. This paper explores Bacon's life and contributions, examining his philosophical ideas, advocacy for scientific advancement, and lasting impact on the development of modern science. В статье представлено глубокое исследование жизни и литературного вклада сэра Фрэнсиса Бэкона, ведущего деятеля английского Возрождения, который произвел революцию в нашем понимании и исследовании мира природы. Как отец эмпиризма, он бросил вызов традиционной аристотелевской логике и отстаивал новый научный метод, основанный на наблюдении, экспериментировании и индуктивном рассуждении. Его новаторская работа, представленная в книге *Novum Organum*, заложила основу научной революции и продолжает влиять на научные исследования сегодня. В этой статье исследуется жизнь и вклад Бэкона, рассматриваются его философские идеи, пропаганда научного прогресса и долгосрочное влияние на развитие современной науки. Maqolada ingliz Uyg'onish davrining yetakchi arbobi bo'lgan ser Frensis Bekonning hayoti va adabiy hissasi haqida chuqur ma'lumot berilgan. U empirizmning otasi sifatida an'anaviy Aristotel mantig'iga qarshi chiqdi va kuzatish, tajriba va induktiv fikrlashga asoslangan yangi ilmiy uslubni qo'llab-quvvatladi. Uning "Novum Organum" da misol keltirgan innovatsion ishi ilmiy inqilobga asos solgan va bugungi kunda ham ilmiy izlanishlarga ta'sir ko'rsatmoqda. Ushbu maqola Bekonning hayoti va hissalarini o'rganadi, uning falsafiy g'oyalari, ilm-fan taraqqiyoti uchun targ'iboti va zamonaviy ilm-fan rivojiga doimiy ta'sirini yoritib beradi.